Intracellular Fate of Hydrophobic Nanocrystal Self‐Assemblies in Tumor Cells. (16th August 2020) - Nicolas‐Boluda, Alba; Yang, Zhijie; Dobryden, Illia; Carn, Florent; Winckelmans, Naomi; Péchoux, Christine; Bonville, Pierre; Bals, Sara; Claesson, Per Martin; Gazeau, Florence; Pileni, Marie Paule
Abstract: Control of interactions between nanomaterials and cells remains a biomedical challenge. A strategy is proposed to modulate the intralysosomal distribution of nanoparticles through the design of 3D suprastructures built by hydrophilic nanocrystals (NCs) coated with alkyl chains. The intracellular fate of two water‐dispersible architectures of self‐assembled hydrophobic magnetic NCs: hollow deformable shells (colloidosomes) or solid fcc particles (supraballs) is compared. These two self‐assemblies display increased cellular uptake by tumor cells compared to dispersions of the water‐soluble NC building blocks. Moreover, the self‐assembly structures increase the NCs density in lysosomes and close to the lysosome membrane. Importantly, the structural organization of NCs in colloidosomes and supraballs are maintained in lysosomes up to 8 days after internalization, whereas initially dispersed hydrophilic NCs are randomly aggregated. Supraballs and colloidosomes are differently sensed by cells due to their different architectures and mechanical properties. Flexible and soft colloidosomes deform and spread along the biological membranes. In contrast, the more rigid supraballs remain spherical. By subjecting the internalized suprastructures to a magnetic field, they both align and form long chains. Overall, it is highlighted that the mechanical and topological properties of the self‐assemblies direct their intracellular fate allowing the control intralysosomal density, ordering, and localization of NCs. Abstract : Controlling interactions between nanomaterials and cells remains a challenge. Here, the intralysosomal distribution of nanocrystals is modulated by using two water‐dispersible architectures of self‐assembled hydrophobic magnetic nanocrystals (NCs): hollow deformable shells (colloidosomes) or solid fcc particles (supraballs). The mechanical and topological properties of the self‐assemblies direct their intracellular fate allowing the control intralysosomal density, ordering, and localization of NCs.